Potensi Aerosol pada Praktik Kedokteran Gigi sebagai Media Penularan Penyakit COVID-19 - Arfi Azkia Firdian; Hidayati Hidayati; Ivony Fitria (Andalas Dental Journal, 2021)
Covid-19 is an infectious disease that attacks the human respiratory system that can cause respiratory infections, ranging from the common cold to serious illnesses, this disease is caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) virus. The process of Covid-19 transmission can occur through direct contact, droplets that are spread through coughs or sneezes from infected people and aerosols in dental care procedures. Aerosols can be generated from dental procedures such as, the use of high-powered tools requiring air pressure and water spray. The purpose of writing is to describe the potential of aerosols in dental practice as a medium for transmission of Covid-19. Aerosols in dental care procedures have the potential to pose a risk in transmitting Covid-19. This is because aerosols are found in the Covid-19 virus which can contaminate surfaces, dental equipment, and the air around the treatment environment which can endanger dentists, staff, and patients.